Synaptic modulation of excitatory synaptic transmission by nicotinic acetylcholine receptors in spinal ventral horn neurons. (2nd April 2015) - Mine, N.; Taniguchi, W.; Nishio, N.; Izumi, N.; Miyazaki, N.; Yamada, H.; Nakatsuka, T.; Yoshida, M.
Highlights: Acetylcholine and nicotine enhance excitatory synaptic transmission in rat spinal ventral horn neurons. nAChRs directly excite and presynaptically facilitate spinal ventral horn neurons. α4β2 receptors, but not α7 receptors, have postsynaptic excitatory actions on spinal ventral horn neurons. Abstract: Nicotinic acetylcholine receptors (nAChRs) are distributed widely in the central nervous system and play important roles in higher brain functions, including learning, memory, and recognition. However, functions of the cholinergic system in spinal motoneurons remain poorly understood. In this study, we investigated the actions of presynaptic and postsynaptic nAChRs in spinal ventral horn neurons by performing whole-cell patch-clamp recordings on lumbar slices from male rats. The application of nicotine or acetylcholine generated slow inward currents and increased the frequency and amplitude of spontaneous excitatory postsynaptic currents (sEPSCs). Slow inward currents by acetylcholine or nicotine were not inhibited by tetrodotoxin (TTX) or glutamate receptor antagonists. In the presence of TTX, the frequency and amplitude of miniature excitatory postsynaptic currents (mEPSCs) were also increased by acetylcholine or nicotine. A selective α4β2 nicotinic receptor antagonist, dihydro-β-erythroidine hydrobromide (DhβE), significantly decreased nicotine-induced inward currents without affecting the enhancement of sEPSCs and mEPSCs. In addition, a selective α7 nicotinic receptor antagonist, methyllycaconitine, did not affect either nicotine-induced inward currents or the enhancement of sEPSCs and mEPSCs. These results suggest that α4β2 AChRs are localized at postsynaptic sites in the spinal ventral horn, non-α4β2 and non-α7 nAChRs are located presynaptically, and nAChRs enhance excitatory synaptic transmission in the spinal ventral horn.